Cross-coupling reactions of aryldiazonium salts with allylsilanes under merged gold/visible-light photoredox catalysis - Akram, Manjur O.; Mali, Pramod S.; Patil, Nitin T. (Organic Letters, 2017)
A method for the cross-coupling reactions of aryldiazonium salts with trialkylallylsilanes via merged gold/photoredox catalysis is described. The reaction is proposed to proceed through a photoredox-promoted generation of an electrophilic arylgold(III) intermediate that undergoes transmetalation with allyltrimethylsilane to form allylarenes.

Synthesis of meta-substituted monodentate phosphinite ligands and implication in hydroformylation - Deshmukh, Satej S.; Gaikwad, Shahaji R.; Pandey, Swechchha; Mali, Pramod S.; Chikkali, Samir H. (Journal of Chemical Sciences, 2017)
Synthesis of meta-substituted phosphinite ligands 3,3'-(methoxyphosphanediyl) bis(N, N-diethylaniline) (4a) and methoxybis(3-methoxyphenyl) phosphane (4b), in high yields, has been demonstrated. Typical phosphorus chemical shift between 110-120 ppm, appearance of methoxy protons and corresponding carbon, as well as ESI-MS spectra unambiguously confirmed the existence of phosphinite ligands 4a and 4b. To demonstrate the synthetic usefulness of 4a and 4b, these ligands were tested in the rhodium catalyzed hydroformylation of 1-octene. The diethylamine substituted ligand 4a was found to be highly active, whereas 4bwas less reactive but revealed slightly better regioselectivity of 62% under optimized conditions. Additionally, 4a and 4b were found to catalyze the hydroformylation of styrene, 1-undecenol and 1,1-disubstituted functional olefin, methyl methacrylate. Both the ligands displayed excellent conversion of styrene, and 4b revealed an excellent branch selectivity of 75%. Although 1-undecenol proved to be amenable to hydroformylation (85-90% conversion to aldehyde), both the ligands failed to discriminate between the linear and branched products. Substrate methyl methacrylate proved to be highly challenging and reduced conversion (between 33-42%) was observed under optimized conditions. Ligand 4a was found to be highly selective towards linear aldehyde (81% linear selectivity).

Tf2NH-catalyzed 1,6-conjugate addition of vinyl azides with p-quinone methides: a mild and efficient method for the synthesis of β-bis-arylamides - Rathod, Jayant; Sharma, Brijesh M.; Mali, Pramod S.; Kumar, Pradeep (Synthesis, 2017)
Tf2NH-catalyzed tandem 1,6-conjugate addition/Schmidt type rearrangement using vinyl azides and p-quinone methides to access a variety of β-bis-arylated amides is reported. The method is quick, efficient, mild, and high yielding with broad substrate scope.